Management of Massive Pulmonary Hemorrhage Following Pulmonary Endarterectomy - YILDIZELİ, BEDRETTİN (GEORG THIEME VERLAG KG, 2014)
Massive pulmonary hemorrhage is a potentially fatal complication of pulmonary endarterectomy. We describe a successful management in which the patient's right lower lobe bronchus was occluded with a Fogarty balloon catheter while on peripheral venoarterial extracorporeal membrane oxygenation.
Keywords: pulmonary endarterectomy; extracorporeal membrane oxygenation; postoperative care; INTERNATIONAL PROSPECTIVE REGISTRY; EXTRACORPOREAL LIFE-SUPPORT; THROMBOENDARTERECTOMY; EXPERIENCE